To find the product of \((23g^2 - 6n)^2\) using the area model, we can use the formula for squaring a binomial, which is given by:
\[ (a - b)^2 = a^2 - 2ab + b^2 \]
Here, we can identify:
- \(a = 23g^2\)
- \(b = 6n\)
Applying the formula, we calculate each term:
- \(a^2\): \((23g^2)^2 = 529g^4\)
- \(b^2\): \((6n)^2 = 36n^2\)
- \(-2ab\): \(-2 \cdot (23g^2) \cdot (6n) = -276g^2n\)
Now we can summarize all the components:
- The term that goes in the orange box (which typically represents \(a^2\)) is \(529g^4\).
- The term that goes in the blue box (which typically represents \(b^2\)) is \(36n^2\).
Putting it all together, the product \((23g^2 - 6n)^2\) can be written in standard form as:
\[ 529g^4 - 276g^2n + 36n^2 \]
Thus, the final answer for \((23g^2 - 6n)^2\) in standard form is:
\[ 529g^4 - 276g^2n + 36n^2 \]